2018
DOI: 10.1051/0004-6361/201731841
|View full text |Cite
|
Sign up to set email alerts
|

The environment of the wind–wind collision region of η Carinae

Abstract: Context. η Carinae is a colliding wind binary hosting two of the most massive stars and featuring the strongest wind collision mechanical luminosity. The wind collision region of this system is detected in X-rays and γ-rays and offers a unique laboratory for the study of particle acceleration and wind magneto-hydrodynamics. Aims. Our main goal is to use X-ray observations of η Carinae around periastron to constrain the wind collision zone geometry and understand the reasons for its variability. Methods. We ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…This kind of activity occurs mainly during the Wolf-Rayet (WR) and Luminous Blue Variable (LBV) stages. It has been observed that in binary systems such winds collide producing very energetic signatures such as particle acceleration, X-ray and γ-ray emission (Abdo et al 2010;Hamaguchi et al 2016Hamaguchi et al , 2018Panagiotou & Walter 2018). In this case the material E-mail:dcaldero@astro.puc.cl launched at supersonic speeds on opposite directions collides generating dense shells of compressed shocked material at temperatures typically in the range ∼ 10 6 -10 7 K. However, binaries are not the only environments where stellar winds interact leaving energetic observational signatures.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of activity occurs mainly during the Wolf-Rayet (WR) and Luminous Blue Variable (LBV) stages. It has been observed that in binary systems such winds collide producing very energetic signatures such as particle acceleration, X-ray and γ-ray emission (Abdo et al 2010;Hamaguchi et al 2016Hamaguchi et al , 2018Panagiotou & Walter 2018). In this case the material E-mail:dcaldero@astro.puc.cl launched at supersonic speeds on opposite directions collides generating dense shells of compressed shocked material at temperatures typically in the range ∼ 10 6 -10 7 K. However, binaries are not the only environments where stellar winds interact leaving energetic observational signatures.…”
Section: Introductionmentioning
confidence: 99%
“…The CWB was also detected up to giga-electronvolt energies with the AGILE and Fermi telescopes (Tavani et al 2009;Abdo et al 2010). However, detection of the hard X-ray emission between 10 keV and 20 keV with NuSTAR is somewhat uncertain (Hamaguchi et al 2018;Panagiotou & Walter 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Spectral energy distribution of η Carinae from 1 keV to 100 TeV. The data are from NuStar (Panagiotou & Walter ), Swift/BAT, INTEGRAL, Fermi LAT, and H.E.S.S, and obtained close to periastron. The red points show the results of a simulation of what could be detected by Cherenkov Telescope Array (CTA) (at periastron) assuming that the emission is dominated by π 0 decay modified by photo‐photo absorption in the strong ultraviolet photon field…”
Section: Introductionmentioning
confidence: 99%